Application of Chitosan from Crab Shell Waste (Portunus pelagicus) as a Preservative for Muli Bananas (Musa acuminata L) - Yusmargana, Fuji Astuti; Kurniasih, Nunung; Junitasari, Assyifa (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2025)
Crab shell is one of the wastes generated from the marine product processing industry. However, the utilization is still very low, especially in Cirebon, it is only used as animal feed and even most of it is waste that also pollutes the environment. One of the alternatives for processing crab shells is used as chitosan because the crab shells are rich in chitin. Chitosan is a chitin derivative compound resulting from the deacetylation process. Chitosan can be called a biopolymer that contains the most nitrogen in nature and also has anti-bacterial, non-toxic, and biodegradable properties because this is why chitosan is in great demand in the industry. Chitosan has a very diverse potential such as in the environmental, pharmaceutical and food fields, one of which has the potential to be a safe preservative in food. This study aims to utilize crab shell waste into chitosan as a preservative for Muli bananas. This research is an experimental study using a completely design with six stages including demineralization, deproteination, deacetylation, manufacture of coating solutions with various concentrations (0%, 1%, 1.5%, 2% and 2.5%), coating process and testing. physical. The parameters measured were the degree of deacetylation, the effect of chitosan concentration and physical tests (discoloration). The results showed that the degree of deacetylation of the chitosan obtained was 95.9825%. From the results of the physical test, it was found that the addition of chitosan with concentrations of 1%, 1.5%, 2% and 2.5% in the coating process resulted in the greater concentration of chitosan being added, the longer the ripening process in bananas and causes bananas peels are not easy to brown.